Seminar West Africa vulnerability Ghana - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
High profile seminar in Ghana, Accra, together with parliamentarians and policy makers trying to identify how climate change will affect the country's, and the region's, agriculture sector